Joint input-state estimation in structural dynamics. (March 2016) - Maes, K.; Smyth, A.W.; De Roeck, G.; Lombaert, G.
Abstract: This paper presents a joint input-state estimation algorithm that can be used for the identification of forces applied to a structure and for the extrapolation of the measured data to unmeasured response quantities of interest. The estimation of the input and the system states is performed in a minimum-variance unbiased way, based on a limited number of response measurements and a system model. No prior information on the system input is required, permitting online application of the algorithm. The paper also presents a novel approach for quantification of the estimation uncertainty originating from measurement errors and unknown stochastic excitation, that is acting on the structure besides the forces that are to be identified. The joint input-state estimation algorithm and the uncertainty quantification approach are verified using numerical simulations. Abstract : Highlights: This paper presents a joint input-state estimation algorithm. The algorithm can be used for the identification of forces applied to a structure. The algorithm can be used for the extrapolation of data to unmeasured response quantities. A novel approach for quantification of the estimation uncertainty is presented. The presented methodology is illustrated and verified using numerical simulations.